Agriculture and climate change: Overview - Nelson, Gerald C. (International Food Policy Research Institute, 2009)
If fundamental climate change mitigation and adaptation goals are to be met, international climate negotiations must include agriculture. Agriculture and climate change are linked in important ways, and this brief focuses on three: (1) climate change will have large effects on agriculture, but precisely where and how much are uncertain, (2) agriculture can help mitigate climate change, and (3) poor farmers will need help adapting to climate change. As negotiations get underway in advance of the meeting of the 15th Conference of Parties of the UN Framework Convention on Climate Change in Copenhagen in December 2009, this brief suggests negotiating outcomes for both mitigation and adaptation funding that will support climate change goals while enhancing the well-being of people who manage and depend on agriculture, especially in the developing world.